Unraveling secondary organic aerosol formation from isoprene and toluene mixture - Shijie Han; Zijun Li; Yik Sze Lau; Yang Xiao; Branka Miljevic; Johanna Horchler; Jiangyong Li; Wan-Ping Hu; Hao Wang; Boguang Wang; Zoran Ristovski (npj Climate and Atmospheric Science)
Abstract Interactions between anthropogenic and biogenic volatile organic compounds (AVOCs and BVOCs) widely exist in the atmosphere, but the resultant secondary organic aerosol (SOA) formation is still poorly understood. When the two commonly widespread AVOC and BVOC, toluene and isoprene, coexisted and oxidized, we observed >20% reduction in the SOA yields compared to the predicted ones from linear addition. By resolving the particle mass spectra using positive matrix factorization, we found that SOA formation from the isoprene+toluene mixture was dominated by the isoprene-related (F-ISO-1 and F-ISO-2) and toluene-related (F-TOL-1 and F-TOL-2) factors during the early and later stages, respectively. Additionally, we observed the formation of cross-products (F-MIX) between isoprene and toluene oxidation intermediates, which accounted for ~30% of the total SOA mass on average. The formation of F-MIX was accompanied by the suppression of particulate products (F-ISO-2 and F-TOL-2), which were associated with the oxidation of ISOPOOH and later-stage oxidation of toluene. Overall, our results highlight the complex interplay between BVOCs and AVOCs and the resultant nonlinear SOA formation in real atmospheres.